4.5: A Low Power Consumption Display Solution Based on The Charge Sharing Technology. (26th August 2021) - Sun, Gaoming; Bi, Yuxin; Hao, Kexin; Liu, Rui; Duan, Xin; Sun, Wei; Luo, Xinzhong
Abstract : With the development of display technology, low power consumption of display device is popular. To drive the display panel in the unit, each sub‐pixel in the panel needs to be charged. The more amount of charge for each sub‐pixel, the greater power consumption is needed for the display panel to display images. This paper provides a method to drive the display panel, which can reduce each sub‐pixel's total charge amount in the display panel. In this way, it can reduce the power consumption needed for driving the panel to display images.